Oxidative stress in pediatric diseases associated with the origin of life and growth and development - Zheng, Bo; Fu, Jianhua (Frontiers in Cell and Developmental Biology, 2025)
The presence of oxidative stress and an imbalance in antioxidant mechanisms have been demonstrated in numerous diseases. Furthermore, mounting evidence suggests that the occurrence, progression, and prognosis of certain pediatric diseases linked to the origin of life and growth and development are also associated with oxidative stress. In this review, we systematically analyze the relationship between oxidative stress and various pediatric diseases, proposing new theoretical foundations and therapeutic targets for their treatment.